EFEKTIVITAS INSTRUMEN UJI SOAL HOTS DAN BUDAYA PENGAMBILAN NILAI ULANGAN HARIAN PADA MADRASAH - Iin Nurmayanti; Abdul Basid (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
This study was conducted to examine the design of an assessment instrument based on Higher Order Thinking Skills (HOTS) in the Al-Qur'an Hadith Subject at Madrasah Tsanawiyah (MTs) Class VIII. The implementation of HOTS-based learning in the 2013 Curriculum (K-13) has not been supported by the availability of HOTS-based practice questions in the K-13 Qur'an Hadith textbook. Researchers tested the HOTS-based assessment instrument independently to support the implementation of HOTS-based learning in MTs. The purpose of this study was to describe the HOTS assessment instrument for the subject of Al-Qur'an Hadith class VIII which was developed validly and reliably, to produce a HOTS-based description and assessment question design that was equipped with an assessment grid and rubric as well as to identify the culture or habits of educators in decision making. daily test scores. This study uses a quantitative approach. Data were collected from the HOTS questionnaire technique for the subjects of al-Qur'an Hadith class VIII semester 1 at the Madrasah Tsanawiyah level regarding the material for â€œKugapai Rezeki-Mu dengan Ikhtiarkuâ€ and small-scale and large-scale trial tests. The data were analyzed qualitatively in the expert test phase of the description of the question design and quantitatively by analyzing the small-scale and large-scale trial assessment instruments. The results of this study indicate that the design of the HOTS assessment instrument is in accordance with the guidelines for the preparation of the HOTS-based assessment instrument. The results of the content validity test of the panel of experts were declared valid, namely 0.95. The HOTS assessment instrument developed is valid based on the Pearson Correlation Output for each item because it is above 0.3 and reliable because the small scale reliability is 0.852 and the large scale is 0.886 which means it is greater than 0.7. Meanwhile, educators are not used to taking daily test scores with HOTS-based assessment instruments. Educators must be able to develop self-quality, MGMP must be able to facilitate the sharing of HOTS knowledge, and the Ministry of Religion must conduct guidance and improve the quality of educators as learning evaluators.